TINGKAT RELIGIUSITAS TERHADAP KECURANGAN AKADEMIK PADA MAHASISWA AKUNTANSI DI SEKOLAH TINGGI ILMU EKONOMI (STIE) - Chairun Nisa; Pipin Fitriasari (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2021)
This research aims to analyze the effect of fraud diamond and the level of religiosity onacademic fraud. The population of this research is STIE Madani Balikpapan bachelor degreestudents who have taken semester 4 above. The sampling technique uses purposive samplingand the total sample is 75 respondents. Data collection of this research used questionarymethod. Analysis method is Structural Equation Modeling (SEM) with Partial Least Square(PLS) and SmartPLS 3.0 as analysis tools. The results showed that capability had a positiveeffect on academic fraud. While pressure, opportunity, rasionalization, and the level ofreligiosity do not affect on academic fraud.